TANGGUNG JAWAB ROOM SERVICE SUPERVISOR PADA DEPARTEMENT FOOD AND BEVERAGE SERVICE EMERALD GARDEN INTERNASIONAL HOTEL MEDAN - May Trilady Chrisera Tampubolon; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
A supervisor has an important role in a company, which is responsible as a planner, a supervisor and a tutor. A supervisor is also responsible for his staffs works. This study is aiming to find out about The Room Service Supervisor Responsibilities in F&B Service Departement in Emerald Garden International Hotel Medan. This study uses a qualitative metode of descriptive approach. The Informants on this research are the Supervisor, the Order Takers, and the Waiters. The data was collected by doing observation, interview, and documentations. The result of this study reveals the Room Service Supervisor Responsibilities in the F&B Service Departement in Emerald Garden International Hotel Medan. The Room Service Supervisor Responsibilities on the successful operational covers supervising the staff in every preparation and serving the guests, making schedule, and taking care of the guests complaints.  Keyword : Responsibilities, Supervisor, F&B Service, Room Service.